1970
DOI: 10.1121/1.1912234
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electric Stimulation of the Crossed Olivocochlear Bundle on Single Auditory-Nerve Fibers in the Cat

Abstract: The activity of single auditory-nerve fibers was examined with and without electric stimulation of the crossed olivocochlear bundle (COCB). In the presence of tones at the characteristic frequencies (CF) of the fibers, the effect of COCB stimulation is, in general, to reduce the spike-discharge rate. The time characteristics of the effect were studied for several parameters of the electric shocks, acoustic stimuli, and fiber characteristics. Some effects of COCB stimulation on “spontaneous” and acoustically ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
173
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(186 citation statements)
references
References 3 publications
12
173
0
1
Order By: Relevance
“…As described in Results, when the time courses of these shifts were characterized by a single exponential function, the mean time constant was 516 ms (SD = 186 ms, N = 28). This time constant is much too short to be a Bslow^efferent effect lasting tens of seconds (Sridhar et al, 1995;Cooper and Guinan, 2003), but is longer than expected for Bfast^MOC reflexes, which rise and decay on the order of 100 ms (Wiederhold and Kiang, 1970;Sridhar et al, 1995;. A somewhat slower efferent effect for DPOAEs was demonstrated by Liberman et al (1996) in cats and by Kim et al (2001) The magnitudes of the shifts measured in the current study for SFOAEs are similar to those reported by Kim et al (2001) for DPOAEs.…”
Section: Time Constant Of Postactivator Shiftsmentioning
confidence: 98%
“…As described in Results, when the time courses of these shifts were characterized by a single exponential function, the mean time constant was 516 ms (SD = 186 ms, N = 28). This time constant is much too short to be a Bslow^efferent effect lasting tens of seconds (Sridhar et al, 1995;Cooper and Guinan, 2003), but is longer than expected for Bfast^MOC reflexes, which rise and decay on the order of 100 ms (Wiederhold and Kiang, 1970;Sridhar et al, 1995;. A somewhat slower efferent effect for DPOAEs was demonstrated by Liberman et al (1996) in cats and by Kim et al (2001) The magnitudes of the shifts measured in the current study for SFOAEs are similar to those reported by Kim et al (2001) for DPOAEs.…”
Section: Time Constant Of Postactivator Shiftsmentioning
confidence: 98%
“…When it was first reported (Goldberg and Fernández 1980), the fact that efferents exerted an excitatory action in the mammalian vestibular labyrinth seemed surprising since other studies had shown that efferent actions in auditory and vibratory organs were inhibitory (Wiederhold and Kiang 1970;Russell 1973, 1976;Furukawa 1981;Ashmore and Russell 1982;Art et al 1984). In retrospect, the challenge was to explain how an efferent action based on ionotropic, cholinergic neurotransmission (Bobbin andKonishi 1971, 1974) could give rise to inhibition.…”
Section: Excitatory Nature Of the Responsesmentioning
confidence: 99%
“…In the case auditory or vibratory receptors, the predominant efferent action so produced is an inhibition of afferent activity (Wiederhold and Kiang 1970;Flock and Russell 1973;1976;Furukawa 1981;Ashmore and Russell 1982;Art et al 1984). More heterogeneous responses have been seen in vestibular organs of frogs (Rossi et al 1980(Rossi et al , 1994Bernard et al 1985;Sugai et al 1991) and turtles (Brichta and Goldberg 2000) and include both increases and decreases in afferent discharge.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously outlined a functional scenario for the presumed multipolar cells that receive olivocochlear input (Benson and Brown 1990). Action of olivocochlear fibers on the periphery decreases the responses of auditory nerve fibers (Wiederhold and Kiang 1970;Guinan and Gifford 1988). Olivocochlear branches may compensate for the reduced nerve fiber input by exciting certain multipolar cells of the cochlear nucleus.…”
Section: Convergence Of Type II Type I and Olivocochlear Inputs Ontmentioning
confidence: 99%